Stratigraphic Distribution of Permian Gastropods from Tak Fa Formation in Southern Part of Nakhon Sawan Province, Thailand - Ketwetsuriya, Chatchalerm; Kanjanapayont, Pitsanupong (Bulletin of Earth Sciences of Thailand, 2021)
The Permian carbonate succession in Tak Fa and Takhli district areas of southern Nakhon Sawan province were grouped in the Tak Fa formation of Saraburi group. The rocks comprise limestones, argillaceous limestones with nodular cherts and intercatalation of shale, which yield several species of gastropods including many invertebrate fossils such as fusulinids, sponges, bivalves, calcareous algae, corals, and bryozoans. The section reaches a thickness of 40 meters. The samples of stratified sampling were collected from Khao Noi and Khao Chai Thong measured sections for petrographic determination. Textures of carbonate rocks consist of bioclastic wackestone to packstone. The gastropod assemblage is dominated by typical Late Palaeozoic cosmopolitan genera with bellerophontoids and pleurotomariines. The distribution of these gastropods suggests the presence of three assemblages zones within distinctive lithofacies: Bellerophon sp. – Glabrocingulum sp. zone, Stegocoelia sp. and Gastropod barren zone. This study indicates that the depositional environment was on shelf lagoon within the carbonate platform varying from back reef to deep of carbonate platform.